Literacy Culture in the Islamic Religious Education and the Development of Islam in Indonesia - Firdaus Wajdi (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2020)
Globalization has enabled the development of Islam in one localized region with the help of global movements. What we do not much understand is how Turkish Ulama have contributed to develop Islamic literacy culture to enhance the development of Islam in Indonesia. This paper identified Jamaat Nur Movement who have utilized globalization to establish literacy culture among Indonesian Muslims and introduced the works of Bediuzzaman Said Nursi. Through careful study of this global movement, this study seeks to understand how a global Muslim organization took advantage from globalization and what are the local Muslims responses to it. This is a qualitative research with observation, interview, as well as library research as tools of data collection. The research keen to understand how globalization has become a tool for development of Islamic organization in Indonesia.